Lasting Local Impacts of an Economywide Crisis - Ravallion, Martin (World Bank, Washington, DC, 2012)
The immediate welfare costs of an economywide crisis can be high, but are there also lasting impacts? And are they greater in some geographic areas than others? The authors study Indonesia s severe financial crisis of 1998. They use 10 national surveys spanning 1993 2002, each covering 200,000 randomly sampled households, to estimate the impacts on mean consumption and the incidence of poverty across each of 260 districts. Counterfactual analyses indicate geographically diverse impacts years after the crisis. Proportionate impacts on the poverty rate were greater in initially better off and less unequal areas. In the aggregate, a large share - possibly the majority - of those Indonesians who were still poor in 2002 would not have been so without the 1998 crisis.